Effect of weed and nitrogen management on coriander (Coriandrum sativum L.) yield and economics - O P Sharma, B L Yadav, I Choudhary, S S Yadav, L R Yadav, (Journal of Spices and Aromatic Crops, 2014)
Field experiments were carried out during rabi 2007–08 and 2008–09 to evaluate the effect of different weed management measures and nitrogen (N) application on yield and economics of coriander. Results revealed that two hand weedings (HW) at 20 and 40 days after sowing (DAS) produced the highest seed and straw yields (13.71 and 25.83 q ha-1). The highest net returns (Rs. 55841 ha-1) and B : C ratio (2.39) were also obtained under this treatment. However, it was found to be at par with pendimethalin at 1.0 kg ha-1 + HW at 40 DAS, wherein seed and straw yields of 13.61 and 25.57 q ha-1, respectively were obtained. The highest harvest index of 35.01% as well as the lowest mean weed index of 0.7%, were also observed under pendimethalin at 1.0 kg ha-1 + HW at 40 DAS. Results further revealed that application of N at 75 kg ha-1 significantly increased the seed yield to the extent of 11.9%, 32.7% and 84.3% and net returns by Rs. 7915, Rs. 18366 and Rs. 34536 ha-1 over 50, 25 kg N ha-1 and control, respectively. Correlation studies revealed that seed yield of coriander was significantly and positively correlated with growth and yield attributing characters and nutrient uptake by crop. Based on the response studies, 64.75 kg ha-1 was found to be the optimum level of N for coriander.